The Culture Industry: Selected Essays on Mass Culture (Routledge Classics) - Adorno, Theodor W. 1903-1969; Bernstein, J. (London Routledge, 1991)
The creation of the Frankfurt School of critical theory in the 1920s saw the birth of some of the most exciting and challenging writings of the twentieth century. It is out of this background that the great critic Theodor Adorno emerged. His finest essays are collected here, offering the reader unparalleled insights into Adorno's thoughts on culture. He argued that the culture industry commodified and standardized all art. In turn this suffocated individuality and destroyed critical thinking. At the time, Adorno was accused of everything from overreaction to deranged hysteria by his many detractors. In today's world, where even the least cynical of consumers is aware of the influence of the media, Adorno's work takes on a more immediate significance. The Culture Industry is an unrivalled indictment of the banality of mass culture.